The effects of moderate altitude on circulating thyroid hormones and thyrotropin in training athletes - Koistinen, P.; Martikkala, V.; Karpakka, J.; Vuolteenaho, O.; Leppäluoto, J. (The Journal of Sports Medicine and Physical Fitness, 1996)
OBJECTIVE: To study the effect of moderate altitude on thyroid hormones among training athletes. EXPERIMENTAL DESIGN: Serum total and free triiodothyronine (T3), thyroxine (T4), and thyrotropin (TSH) concentrations were measured among eight training athletes at sea level and subsequently during training for 12 days at the altitude of 1100-2700 m. SETTING: Deaconess Institute of Oulu, and Division of Sports Medicine, Department of Physiology, University of Oulu, Finland. PARTICIPANTS: National top class skiers who normally live at sea level. RESULTS: Serum concentrations of TSH, total and free T4, and reverse T3 did not change significantly. A significant decrease in serum total T3 levels from 1.9 nmol*1-1 on days 1-3 to 1.6-1.7 nmol*l-1 on days and 5-6 (p < 0.05) was observed. Serum albumin decreased (p < 0.05) on days 1-8 at altitude and correlated to serum total T3 (R = 0.36, p = 0.013). Serum free T3 increased steadily at moderate altitude and reached a significantly higher level (p < 0.05) at the end of the training period than before. CONCLUSIONS: The serum free T3 increases when unacclimatized sea level skiers move to train at moderate altitude.